Using interactive graphical and technological strategies for EFL reading comprehension: a case study involving engineering students - Barraza, Julia Valeska (Colombian Applied Linguistics Journal, 2014)
This qualitative case study engaged a group of engineering students in the use of interactive graphical and technological strategies called interactive graphic organisers (IGOs). IGOs are computer software that provide graphic organising support in order to improve the level of reading comprehension among users. The participants were asked to use three different types of IGOs: cause and effect, a sequence of events, and pros and cons while reading texts. Survey data was gathered through an opinion survey with the intention of collecting and evaluating the students’ perceptions of the use of the IGO software. Findings revealed that most of the learners’ opinions expressed that the use of IGOs was effective. Engineering students also expressed that they would have liked more opportunities to use this software. They felt that by using IGOs, they not only improved their reading scores, but also enjoyed their experience using new strategies via the software.